Jual-Beli Tanah Reklamasi Pantai Dalam Tinjauan Pasal 1320 KUHPerdata (Studi Kasus Di Kecamatan Sapeken Kabupaten Sumenep) - Muarif; Supriyo, Agus (UNES Law Review, 2023)
Abstract: Buying and selling land is an agreement where the party who owns the land, called the “seller”, promises and commits himself to handing over his rights to the land in question to another party, called the “buyer”. Based on Article 1457 of Civil Code (KUHPer), sale and purchase is an agreement in which one party binds himself to hand over an item and the other party to pay the promised price. Price can be interpreted as a legal means of certain payment in the form amount of money. In order for an agreement to be valid and binding on the parties, it must fulfill the conditions stipulated in Article 1320 BW, which are: agree by those who bind themselves; Capable of making the agreement, A certain thing, A lawful cause or cause. Reclamation comes from the word “reclamation”, which in English means renewing. Meanwhile, in terms of reclamation, it is a form of effort to expand land or create land that can be utilized, it is of course. Reclamation, which is a process of restoring land and is carried out by opening up new land in coastal areas, has many concepts applied by various countries in the world to utilize coastal areas. The goal of reclamation is to create new land for housing, agriculture, and industry. The reclamation land is most often found in coastal cities to increase housing capacity and build ports.